TORAKOCHIRURGIAAssessment of epidemiological and clinical factors that can influence mediastinal metastatic disease in NSCLC patients qualified for surgical treatment - Dzięgielewski, Piotr; Kozłowski, Mirosław; Nikliński, Jacek; Bernacki, Andrzej; Fiedoruk, Jarosław; Laudański, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background: NSCLC patients still have one of the worst prognoses among all cancer disease patients. New approaches in diagnosis and treatment are insufficient as yet, and there is a necessity of better TNM patient classification algorithms based on viable and invasive staging me-thods together. Aim: To assess factors that may influence metastatic mediastinal involvement in NSCLC patients. Material and methods: 143 consecutive NSCLC patients received mediastinoscopy and 10 patients additionally parasternal left mediastinotomy with enlarged and normal mediastinal lymph nodes as well. Operable cases underwent curable lung tissue resection with lym-phadenectomy. We tried to assess factors that may influence metastatic disease in NSCLC patients. Results: Among examined epidemiological and clinical factors only histological type of adenocarcinoma and increasing T stage of the neoplasm had a significant influence on mediastinal lymph node involvement in NSCLC patients. Conclusions: Patients with adenocarcinoma of the lung more often have mediastinal lymph node involvement than other NSCLC types and the risk grows together with T stage.